Situation Report: Poland, 18 June 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Moscow Summit Hailed Visit of West Berlin Mayor Health Ministry Officials Sentenced for Bribes The Death of Marek Hlasko Economic Relations with Foreign Countries Miscellaneous